The maths book - Karl Warsi; Heather Davis (mathematics teacher); John Farndon; Jonny Griffiths; Tom Jackson 1972; Mukul Pated; Sue Pope 1959 (London : DK Publishing, 2019)
Take a journey through the fascinating story of fractions, numbers, patterns, and shapes in order to better understand the complex world we live in. Continuing the "Big Ideas" series' trademark combination of authoritative, clear text and bold graphics to chart the development of maths through history, the book explores and explains some of the most complex and fascinating mathematical subjects. Delve into everything from the mathematical ideas and inventions of the ancient world such as the first number systems, magic squares, and the Chinese abacus, through to the developments in mathematics during medieval and Renaissance Europe, to the rise of group theory and cryptography more recently. This diverse and inclusive account of mathematics will have something for everybody- for those interested in the maths behind world economies, secret spies, modern technology and plenty more, taking readers around the world from Babylon to Bletchley Park. Tracing maths through the Scientific Revolution to its 21st-century use in computers, the internet, and AI, The Maths Book uses an innovative visual approach to make the subject accessible to everyone, casual readers and students alike.
Includes index
Keywords: Mathematics -- Popular works